Makna Avatar Couple pada Pengguna Media Sosial Discord - Risman Maulana; Anne Maryani (UNISBA Press, 2022)
Abstract. Couple avatars have become one of the things that we often encounter, especially when we browse the internet. Not infrequently we encounter photos or two-dimensional avatars that show like a couple. In this study, the researchers wanted to dig deeper into the relationship between this avatar couple for discord social media users. The purpose of this research is to find out how the motives, experiences, and also the meaning of the avatar couple users in using the avatar couple. The method used in this study is a qualitative method with a phenomenological study approach which is also supported by the theory of symbolic interactionism. The subject of this research is of course the avatar couple users on Discord social media where they are included in the Discord server, Buddy Genshin. Data collection techniques in this study used in-depth interviews, and observation. Based on the results of the study, it was found that the motives of discord social media users in using the avatar couple were seeking attention, and giving a sense of security, being invited by a partner, being forced, and seeing other people. The experiences gained while using the avatar couple include a change in interaction which then from this interaction change gives a negative value and a positive value which in the end gives a response in the form of feelings of pleasure, sadness, happiness, discomfort and shame. Then the meaning of the avatar couple users was also found. This means that it has the meaning of showing the existence of a relationship, which is further elaborated in the form of a sense of love and security in the form of validation, a form of sense of belonging and status clarification. Abstrak. Avatar couple telah menjadi salah satu hal yang cukup sering kita temui, terkhusus ketika kita berjelajah lewat internet. Tidak jarang kita temui foto-foto atau avatar dua dimensi yang menunjukkan layaknya sepasang kekasih. Pada penelitian ini peneliti ingin menggali lebih dalam lagi terkait daripada avatar couple ini bagi para pengguna media sosial discord. Tujuan dari dilakukannya penelitian ini adalah untuk mengetahui bagaimana motif, pengalaman, dan juga makna dari para pengguna avatar couple dalam menggunakan avatar couple. Metode yang digunakan dalam penelitian ini yaitu menggunakan metode kualitatif dengan pendekatan studi fenomenologi yang didukung juga oleh teori interaksionisme simbolik. Subjek dari penelitian ini yaitu tentunya para pengguna avatar couple pada media sosial Discord yang mana mereka termasuk kedalam server Discord Sobat Genshin. Teknik pengumpulan data dalam penelitian ini menggunakan wawancara mendalam, dan observasi. Berdasarkan hasil penelitian, ditemukan bahwa motif dari pengguna media sosial discord dalam menggunakan avatar couple yaitu mencari perhatian, dan memberikan rasa aman, diajak oleh pasangan, terpaksa, dan karena melihat orang lain. Pengalaman yang didapatkan selama menggunakan avatar couple diantaranya adalah terjadi perubahan interaksi yang kemudian dari perubahan interaksi ini memberikan nilai negatif dan nilai positif yang pada akhirnya memberikan respon berupa perasaan senang, sedih, bahagia, risih dan malu.Kemudian ditemukan juga makna dari para pengguna avatar couple ini yaitu memiliki makna sebagai menunjukkan adanya suatu hubungan, dimana dijabarkan lebih dalam lagi berupa adanya rasa cinta dan aman ke dalam bentuk validasi, bentuk sense of belonging dan penjelesan status.